You are on page 1of 8

c   



   .

     .

 .

         .

 .

    c  .

     .

.

 .

 .

.

   .

     .

.

     c  .

    .

 !      .

.

.

 "     .

    .

     .

.

   .

  .

 #c  .

 .

$    %   .

.

    &       '   c     &    .

 .

  .

  .

.

(' )      .

 &.

   .

      c   .

  .

  *   .

        .

.

      *  .

        c     .

  .

 .

   .

'    .

#  .

$.

       +       # .$  .

-  .

 .

 .

'#*  .

 .

.

.

 $.c         %   .

.

    &       '   c     &    .

 .

  .

  .

.

(' )      .

 &.

   .

     c     .

   .

     .

 .

         .

 .

   c  .

     .

.

 .

 .

.

   .

     .

.

    c  .

    .

 !      .

.

.

 "     .

    .

     .

.

   .

  .

 #c  .

 .

$  %   .

.

    &       '   c     &    .

 .

  .

  .

.

(' )      .

 &.

   .

    .

v    .

indicates direction) ˜9 vf = vi + a*t 0 vf = 0 + (-9  m/s)*( 6 s) ˜ vf = -  m/s (.   ˜ Given: a = +3  m/s Find: t = 3  s d = ?? vi = 0 m/s   d = vi*t + 0 *a*t 3  d = (0 m/s)*(3  s)+ 0 *(3 0 m/s)*(3  s) 4  d = ˜0 m   eturn to Problem ˜ 6  Given: d = ˜˜0 m Find: t =  ˜ s a = ?? vi = 0 m/s   d = vi*t + 0 *a*t 9  ˜˜0 m = (0 m/s)*( ˜ s)+ 0 *(a)*( ˜ s) ˜0 ˜˜0 m = (˜3  s)*a ˜˜ a = (˜˜0 m)/(˜3  s) ˜ a =  ˜0 m/ s ˜3 eturn to Problem  ˜4  ˜  Given: a = -9  m Find: t=6s d = ?? vi = 0 m/s vf = ?? ˜6 d = vi*t + 0 *a*t ˜ d = (0 m/s)*( 6 s)+ 0 *(-9  m/s)*( 6 s) ˜ d = -33 m (.indicates direction)  eturn to Problem 3 3  4  Given: vi = ˜  m/s Find: vf = 46 ˜ m/s t =  4 s d = ?? a = ?? .

 a = (Delta v)/t 6 a = (46 ˜ m/s .0 m/s)/(˜ 0 s) 4 a = 4 m/s 4 d = vi*t + 0 *a*t 49 d = (0 m/s)*(˜ 0 s)+ 0 *(4 m/s)*(˜ 0 s) 0 d = 0 m + 400 m ˜ d = 400 m  (Note: the d can also be calculated using the equation vf = vi + *a*d) 3 eturn to Problem 6 4    Given: vi = 0 m/s Find: vf =  ˜0 m/s d = 3 4 m 6 vf = vi + *a*d  ( ˜0 m/s) = (0 m/s) + *(a)*(3 4 m) a = ?? .˜  m/s)/( 4 s)  a = ˜˜  m/s  d = vi*t + 0 *a*t 9 d = (˜  m/s)*( 4 s)+ 0 *(˜˜  m/s)*( 4 s) 30 d = 4  m + 34 ˜ m 3˜ d = 9  m 3 (Note: the d can also be calculated using the equation vf = vi + *a*d) 33 eturn to Problem 4 34  3  Given: vi = 0 m/s Find: d = -˜ 40 m a = -˜ 6 m/s t = ?? 36 d = vi*t + 0 *a*t 3 -˜ 40 m = (0 m/s)*(t)+ 0 *(-˜ 6 m/s)*(t) 3 -˜ 40 m = 0+ (-0 3 m/s)*(t) 39 (-˜ 40 m)/(-0 3 m/s) = t 40 ˜ 6 s = t 4˜ t = ˜ 9 s 4 eturn to Problem  43  44  Given: vi = 0 m/s Find: vf = 44 m/s a = ?? t = ˜ 0 s d = ?? 4 a = (Delta v)/t 46 a = (444 m/s .

 0 4 m/s = (0 m/s) + (0  m)*a 9 (0 4 m/s)/(0  m) = a 60 a = 0 ˜ m/s 6˜ eturn to Problem  6  63  Given: vi = 0 m/s Find: vf = 6 m/s a = 3 m/s d = ?? 64 vf = vi + *a*d 6 (6 m/s) = (0 m/s) + *(3 m/s)*d 66 4 m/s = (0 m/s) + (6 m/s)*d 6 (4 m/s)/(6 m/s) = d 6 d = 04 m 69 eturn to Problem  0  ˜  Given: vi =  4 m/s Find: vf = 0 m/s d = ?? t =   s  d = (vi + vf)/ *t 3 d = ( 4 m/s + 0 m/s)/ *  s 4 d = (˜˜  m/s)*  s  d =  6 m 6 eturn to Problem 9     Given: a = -9  m/s Find: vf = 0 m/s vi = ?? d =  6 m 9 vf = vi + *a*d 0 (0 m/s) = vi + *(-9  m/s)*( 6 m) ˜ 0 m/s = vi .˜ 3 m/s  ˜ 3 m/s = vi 3 vi =  ˜ m/s 4 eturn to Problem ˜0   6  Given: a = -9  m/s Find: vf = 0 m/s d = ˜ 9 m vi = ?? .

  m/s 90   m/s = vi 9˜ vi =  03 m/s 9 o find hang time.t = ??  vf = vi + *a*d  (0 m/s) = vi + *(-9  m/s)*(˜ 9 m) 9 0 m/s = vi .30 6 m/s vi = 30 6 m/s Now use: vf = vi + *a*d (0 m/s) = (30 6 m/s) + *(-9  m/s)*(d) . find the time to the peak and then double it 93 vf = vi + a*t 94 0 m/s =  03 m/s + (-9  m/s)*tup 9 - 03 m/s = (-9  m/s)*tup 96 (- 03 m/s)/(-9  m/s) = tup 9 tup = 0 ˜3 s 9 hang time = ˜ 03 s 99 eturn to Problem ˜˜ ˜00  ˜0˜  Given: vi = 0 m/s Find: vf = ˜ m/s a = ?? d = 0 40 m ˜0  vf = vi + *a*d  ˜03  (˜ m/s) = (0 m/s) + *(a)*(0 40 m) ˜04  ˜44˜ m/s = (0 m/s) + (˜ 6 m)*a ˜0  (˜44˜ m/s)/(˜ 6 m) = a ˜06  a = ˜ 6*˜0 m /s ˜0  eturn to Problem ˜ ˜0  ˜09  Given: a = -9  m/s Find: vf = 0 m/s t = 3 ˜3 s d = ?? ˜  (NO: the time required to move to the peak of the trajectory is one-half the total hang time ) First use: vf = vi + a*t 0 m/s = vi + (-9  m/s)*(3 ˜3 s) 0 m/s = vi .

0 m/s = (93 m/s) + (-˜9 6 m/s)*d -93 m/s = (-˜9 6 m/s)*d (-93 m/s)/(-˜9 6 m/s) = d d = 4 9 m eturn to Problem ˜3 ˜˜0  Given: Find: vi = 0 m/s ˜˜  ˜˜9  d = -30 m a = -9  m/s ˜˜˜  d = vi*t + 0 *a*t ˜˜  -30 m = (0 m/s)*(t)+ 0 *(-9  m/s)*(t) ˜˜3  -30 m = 0+ (-4 9 m/s)*(t) ˜˜4  (-30 m)/(-4 9 m/s) = t ˜˜    s = t ˜˜6  t =  69 s eturn to Problem ˜4 ˜˜  Given: Find: vi = 36 m/s ˜  ˜9  t = ?? vf = 0 m/s a = ?? d = 0 06˜ m ˜0  vf = vi + *a*d ˜˜  (0 m/s) = (36 m/s) + *(a)*(0 06˜ m) ˜  0 m/s = (˜3469 m/s) + (0 ˜4 m)*a ˜3  -˜3469 m/s = (0 ˜4 m)*a ˜4  (-˜3469 m/s)/(0 ˜4 m) = a ˜  a = -˜ 0*˜06 m /s ˜6  (he .sign indicates that the bullet slowed down ) ˜  eturn to Problem ˜ Given: Find: a = -9  m/s t = 3 4˜ s ˜3˜  vi = 0 m/s ˜30  d = vi*t + 0 *a*t d = (0 m/s)*(3 4˜ s)+ 0 *(-9  m/s)*(3 4˜ s) d = ?? .

6 m/s ˜4˜  6 m/s = vi ˜4  vi = 4 6 m /s ˜43  eturn to Problem ˜ Given: vi = 0 m/s vi = ?? d = 90 m Find: vf =  3 m/s a = ?? d = ˜36 m t = ?? ˜  ˜  ˜46  vf = vi + *a*d ˜4  ( 3 m/s) = (0 m/s) + *(a)*(˜36 m) ˜4  9 m/s = (0 m/s) + (30 m)*a ˜49  9 m/s = (30 m)*a ˜0  (9 m/s)/(30 m) = a ˜˜  a =  6 m/s ˜  vf = vi + a*t ˜3   3 m/s = 0 m/s + ( 6 m/s)*t ˜4  ( 3 m/s)/( 6 m/s) = t ˜  t = 30  s eturn to Problem ˜ ˜6  Given: vi = 0 m/s Find: vf = ˜˜ m/s d = 39 m ˜9  vf = vi + *a*d  ˜60  (˜˜ m/s) = (0 m/s) + *(a)*(39 m) ˜6˜  ˜44 m/s = 0 m/s + (96 m)*a ˜6  ˜44 m/s = (96 m)*a ˜63  (˜44 m/s)/(96 m) = a ˜64  a = ˜  m/s a = ?? .˜3  ˜34  ˜36  ˜3  d = 0 m+ 0 *(-9  m/s)*(˜˜ 63 s) ˜33  d = - 0 m (NO: the .sign indicates direction) ˜3  eturn to Problem ˜6 Given: a = -3 90 m/s ˜44  ˜4  Find: vf = 0 m/s ˜3  vf = vi + *a*d ˜39  (0 m/s) = vi + *(-3 90 m/s)*(90 m) ˜40  0 m/s = vi .

˜93 m/s ˜  ˜93 m/s = vi ˜3  vi = 4 3 m/s Now convert from m/s to mi/hr: ˜4  ˜  vi = 4 3 m/s * ( 3 mi/hr)/(˜ m/s) vi = 94 4 mi/hr ˜6  ˜  eturn to Problem 0  . find speed in units of m/s: ˜69  vf = vi + *a*d  ˜0  (0 m/s) = vi + *(-9  m/s)*(9˜  m) ˜˜  0 m/s = vi .˜6  ˜66  ˜6  eturn to Problem ˜9 Given: Find: a = -9  m/s vf = 0 m/s d = 9˜  m vi = ?? t = ?? ˜6  First.